2015
DOI: 10.1002/14651858.cd010896.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Regional Cerebral Blood Flow Single Photon Emission Computed Tomography for detection of Frontotemporal dementia in people with suspected dementia

Abstract: At present, we would not recommend the routine use of rCBF SPECT in clinical practice because there is insufficient evidence from the available literature to support this.Further research into the use of rCBF SPECT for differentiating FTD from other dementias is required. In particular, protocols should be standardised, study populations should be well described, the threshold for 'abnormal' scans predefined and clear details given on how scans are analysed. More prospective cohort studies that verify the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…A change to regional blood flow on SPECT is another red flag for underlying brain pathology. However, SPECT reporting is not standardised between centres and its specificity for dementia is only around 73% 33 34. Some centres use fludeoxyglucose positron-emission tomography during a work-up for dementia, which is more sensitive and specific than SPECT 23.…”
Section: Investigationsmentioning
confidence: 99%
“…A change to regional blood flow on SPECT is another red flag for underlying brain pathology. However, SPECT reporting is not standardised between centres and its specificity for dementia is only around 73% 33 34. Some centres use fludeoxyglucose positron-emission tomography during a work-up for dementia, which is more sensitive and specific than SPECT 23.…”
Section: Investigationsmentioning
confidence: 99%
“…Whilst the SPECT scan is widely requested for the diagnosis of FTD, the clinical evidence for its use is still lacking [28]. This type of investigation was the only FTD-specific nonclinical benchmark identified in the study and its overall performance was positive, albeit with a substantial number of occasions where its negative findings severely delayed the diagnosis.…”
Section: The Art and Power Of A Request Formmentioning
confidence: 98%
“…However, there is a mixed picture in the literature concerning these scans, with their considerable limitations [26,27]. A recent meta-analysis revealed that there is currently insufficient evidence to recommend the use of SPECT scans in routine practice [28]. EEG may be helpful [29][30][31] but it is not usually employed in a dementia clinic.…”
Section: The Variability and Inaccuracy Of The Diagnostic Criteriamentioning
confidence: 99%
“…Another method for functional imaging is perfusion SPECT, which also requires the intravenous injection of a radiolabeled tracer molecule, but instead is a measure of cerebral blood flow (CBF). The radiotracers most commonly used are 99m technetium-hexamethylpropylenamine oxime ( 99m Tc-HMPAO) or 99m technetium-ethyl-cysteinate dimer ( 99m Tc-ECD) (Archer et al, 2015).…”
Section: Imaging Techniques To Diagnose Ftdmentioning
confidence: 99%